2018
DOI: 10.1038/s41419-018-0625-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming of acute lymphoblastic leukemia cells in response to glucocorticoid treatment

Abstract: Glucocorticoids (GCs) are metabolic hormones with immunosuppressive effects that have proven effective drugs against childhood acute lymphoblastic leukemia (ALL). Yet, the role of metabolic reprogramming in GC-induced ALL cell death is poorly understood. GCs efficiently block glucose uptake and metabolism in ALL cells, but this does not fully explain the observed induction of autophagy and cell death. Here, we have performed parallel time-course proteomics, metabolomics, and isotope-tracing studies to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 57 publications
3
37
0
4
Order By: Relevance
“…Standard treatment of B-ALL is the administration of synthetic glucocorticoids (GC) to slow down cellular glucose intake and induce cell death [127]. Following GC treatment in B-ALL, there is a reduction in glucose and glutamine cellular intake but unexpectedly an increase of glutamine synthesis [128]. Dyczynski et al showed that in the absence of normal nutrient intake, there is increased autophagic flux to catabolically make up for the lost nutrients; a byproduct of this catabolism, ammonia, is then utilized by glutamate–ammonia ligase to synthesize glutamine intracellularly, allowing the cells to provide their own glucose supply [128].…”
Section: Autophagy Plays Context-dependent Roles In Leukemia Initimentioning
confidence: 99%
“…Standard treatment of B-ALL is the administration of synthetic glucocorticoids (GC) to slow down cellular glucose intake and induce cell death [127]. Following GC treatment in B-ALL, there is a reduction in glucose and glutamine cellular intake but unexpectedly an increase of glutamine synthesis [128]. Dyczynski et al showed that in the absence of normal nutrient intake, there is increased autophagic flux to catabolically make up for the lost nutrients; a byproduct of this catabolism, ammonia, is then utilized by glutamate–ammonia ligase to synthesize glutamine intracellularly, allowing the cells to provide their own glucose supply [128].…”
Section: Autophagy Plays Context-dependent Roles In Leukemia Initimentioning
confidence: 99%
“…While tremendous progress has been made in the treatment of pediatric ALL, the success rate of current treatments is much more modest in adults ( Aldoss and Stein, 2018 ). Hence, new therapeutic agents are urgently needed for ALL therapy ( Thu Huynh and Bergeron, 2017 ; Dyczynski et al., 2018a ). The antifungal, anticancer, and antinociceptive effects of diorcinol have been investigated in previous studies ( Gao et al., 2013 ; Li et al., 2015 ; Zhuravleva et al., 2016 ; Li et al., 2018 ; Zhang et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The functional impact of GCs on cALL cell metabolism in vitro is demonstrated by proving that GCs reduce nucleotide, polyamine, and fatty acid synthesis. Concomitantly, GCs induce glutamine and phosphatidylcholine synthesis as well as FAO shifting the entire mitochondrial fuel programme 57 . Furthermore, dexamethasone can decrease glycolysis and enhance OxPhos and mitochondrial turnover through autophagy in pediatric T‐ALL cell lines 58 …”
Section: Cell Metabolism In Callmentioning
confidence: 99%